Evaluation of Patient Satisfaction Towards Pharmacy Services at Hospital Outpatient Pharmacies in Padang - Sara Surya; Sefrianita Kamal; Lusia Eka Putri (Borneo Journal of Pharmacy, 2019)
Patient satisfaction with the quality of pharmaceutical services is an essential indicator in the variety of health services in hospitals. Service quality is said to be enjoyable and satisfying if the services received are by or exceeding expectations. Otherwise, service quality is supposed to be inadequate or unsatisfactory if the service received is lower than expected. This study aims to determine the percentage level of patient satisfaction with pharmacy services at hospital outpatient pharmacies in Padang and to find out the pharmaceutical service system carried out by pharmacists on duty at hospital outpatient pharmacies that were located in Padang. This study used descriptive data collection. Satisfaction was assessed by giving questionnaires to respondents, and then the surveys were analyzed descriptively. Assessment of patient satisfaction was conducted by taking data through a poll of 100 respondents. Satisfaction analysis was carried out using a Likert scale, and then the data was displayed in the cartesian form.